Exploring the therapeutic potential of “Xiaochaihu Decoction”: a systematic review and meta-analysis on the clinical effectiveness and safety in managing cancer-related fever - Bu, Zhijun; Xu, Yaoyu; Zhou, Xian; Wang, Xuefeng; Liu, Shuyuan; Wang, Linyan; Yang, Bei; Zhou, Xiaodie; Lu, Guanhang; Liu, Jianping; Liu, Zhaolan (Frontiers in Pharmacology, 2024)
Objective: This study aimed to conduct the first meta-analysis to comprehensively evaluate the clinical effectiveness and safety of Xiaochaihu Decoction in treating Cancer-related Fever (CRF). Methods: Eight databases were systematically searched in September 2023. The risk of bias (ROB) 2.0 tool recommended by Cochrane Handbook was applied to evaluate the ROB of the included randomized controlled trials (RCTs). Additionally, the quality of evidence was assessed using the Grading of recommendations assessment, development and evaluation (GRADE) tool. Results: We included 18 RCTs involving 1424 patients. Compared to Western medicine or Xinhuang Tablets, Xiaochaihu Decoction significantly improved clinical effectiveness in CRF patients (risk ratio [RR] = 1.24, 95% confidence interval [CI]: 1.17, 1.32) and expedited the normalization of body temperature (mean difference [MD] = -5.29, 95%CI: -5.59, -4.99). It also demonstrated a reduction in tumor necrosis factor-α (TNF-α) levels (MD = -0.63, 95%CI: -0.84, -0.41) and an increase in IL-2 levels (MD = 1.42, 95%CI: -1.09, 1.74). Analysis of Karnofsky Performance Status (KPS) scores showed that the use of Xiaochaihu Decoction improved the quality of life in CRF patients (RR = 1.57, 95%CI: 1.11, 2.22) and reduced the incidence of adverse events. However, it is important to note that the majority of included studies showed "some concerns" in risk of bias based on ROB 2.0, and the evidence quality assessed by GRADE method was rated as "low". Conclusion: While this study suggests the clinical effectiveness and safety of Xiaochaihu Decoction in treating patients with CRF, confirming these findings will necessitate additional high-quality, large-scale RCTs in future research. Systematic review registration: https://www.crd.york.ac.uk/prospero/, identifier: CRD42023484068.